Agricultural Socialization’ Influence on the Rice Farmers’ Farming Behavior in Noelbaki Village - Bulkis Bulkis (Indonesian Journal of Multidisciplinary Science, 2023)
The availability of food in sufficient quantities, good quality of foodstuffs, and high nutritional value have a broad impact on the economy and the quality of human resources. Extension workers are one of the factors that cause development potential both in quantity and quality. Indonesia faces the fact that the number of extension workers is still lacking and the quality cannot be said to be adequate so it still needs to be developed. Based on the problems that have been formulated above, the objectives of the study are analyzing the farming behavior of rice farmers and the empowerment of farmers through counseling in an effort to increase the productivity of paddy rice. The results of the study on the level of paddy rice productivity in Noelbaki are high. One of the factors that cause the high productivity of rice is the increase in the ability of farmers to manage rice farming and allocate their resources and farmers' knowledge about the use of technology has also increased. The effect of counseling on the level of rice paddy productivity is positive because it has an impact on changing the behavior of farmers. The higher the empowerment through paddy rice farming counseling, the higher the productivity results achieved.